How Flexible Are Wages in Response to Local Unemployment in South Africa? - Kingdon, G; Knight, J (2006)
It is commonly claimed that the South African labor market is unusually inflexible owing to the strength of the country's unions and the system of centralized collective bargaining. One sign of labor market inflexibility is low responsiveness of wages to local unemployment. Analyzing data from the South African Living Standards Survey, the authors find that the elasticity of wages with respect to local unemployment rates in South Africa in 1993 was about -0.1. The similarity of this elasticity to that found in other countries, including the United States and the United Kingdom, is surprising given South Africa's national unemployment rate of over 30%. The wage curve elasticity persists over a much wider range of unemployment rates in South Africa than in OECD countries, implying that unemployment in South Africa can have a large impact on wages.